The Behaviors, Benefits, and Barriers of Humanitarian Aid Leader Humility. Issue 3 (September 2019) - Shannonhouse, Laura R.; Mize, Mary Chase Breedlove; Hall, M. Elizabeth Lewis; Aten, Jamie D.; Wang, David C.; Davis, Edward B.; Van Tongeren, Daryl R.
This study explores how humility is contextualized in the culture of faith-based humanitarian aid leadership. Consensual Qualitative Research was used to synthesize the personal and observational experiences of 13 humanitarian aid leader exemplars. Characteristics and behaviors of humble leaders are discussed, along with the benefits of humble leadership on aid workers, local partners, and recipients of humanitarian aid services. A theistic dimension of humility is noted along with an outcome pathway for humble practice which considers barriers native to the humanitarian aid context.